Perkembangan Desa Wisata Pangsan Sebagai Destinasi Pariwisata Di Kecamatan Petang Badung - Adikampana, I Made; Parashita, Ni Luh Laksmi (JURNAL DESTINASI PARIWISATA; Vol 5 No 1 (2017): VOL 5, NO 1 (2017): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2018)
This report, entitled "Development of Pangsan Village Tourism as Destinations in Petang District of Badung Regency" with the background of the issue stating that the tourist village near death, or it can be said as a tourist village that did not develop. This study aims to determine the involvement of what has been made public for five years after the enactment of a tourist village and how the development of village tourism with the involvement of the community as the manager of the tourist village through analysis of the Destinations Lifecycle Theory. Judging from Destinations Lifecycle theory, Pangsan Village Tourism stage of development at the stage of Involvement / participation is increasing visitors encouraged local residents offers exclusively to its visitors. Contact with local community remain high and some of them began to adjust their social patterns to accommodate changes in economic conditions due to the presence of tourists. Promotion of tourist destinations ranging initiated. During the process of collecting the data, obtained by the findings that the involvement or participation in a tourist village in the management of member services, guides, to provide lodging for travelers when visiting tourist village. In addition, people began to provide other facilities such as trekking and cycling facilities as well as the efforts rafting prepared by one of the people. Keywords: Tourism Village, Involvement, Development